2008
DOI: 10.1002/j.2161-4296.2008.tb00421.x
|View full text |Cite
|
Sign up to set email alerts
|

The Desert Ant's Navigational Toolkit: Procedural Rather than Positional Knowledge

Abstract: Desert ants, Cataglyphis in North Africa and Melophorus in Central Australia, exhibit amazing feats of navigation. This essay focuses on the architecture of the insect's navigational toolkit. First, path integration (PI) is the ant's major means of navigation, at least in so far as it is running all the time while the animal is on its foraging journey, irrespective of whether landmark‐based systems of navigation (LN) are expressed as well. Its two components, compass and odometer, are discussed. Second, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 53 publications
0
60
0
Order By: Relevance
“…As mentioned above, the main navigational toolkit of Cataglyphis is path integration (Ronacher, 2008;Wehner, 2008). To determine the direction of their home vectors, the ants mainly rely on celestial cues, especially the polarization pattern and the azimuthal position of the sun (Wehner and Müller, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the main navigational toolkit of Cataglyphis is path integration (Ronacher, 2008;Wehner, 2008). To determine the direction of their home vectors, the ants mainly rely on celestial cues, especially the polarization pattern and the azimuthal position of the sun (Wehner and Müller, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, these few studies document thatlike flying insects -some ant species exhibit a striking behavioral sequence at the beginning of their foraging life. Desert ants in particular, which are well known for their navigational performance (Ronacher, 2008;Wehner, 2008;Wehner and Rössler, 2013;Wehner et al, 1996), use a considerable amount (up to 3 days; Fleischmann et al, 2016;Stieb et al, 2012) of their short lives (often less than a week; Schmid-Hempel and Schmid-Hempel, 1984) outside the nest to perform learning walks. Cataglyphis ants are thermophilic scavengers searching for dead arthropods during their extensive foraging excursions.…”
Section: Introductionmentioning
confidence: 99%
“…This is the central question we have addressed in the present study. We already know that landmark guidance (LGmediated behaviour) can take precedence over fully paying out the home vector (HV-mediated behaviour) (Wehner, 2008;Cheng et al, 2009;Wehner, 2009), and that even when this is the case, the path integrator keeps running in the background (Sassi and Wehner, 1997;Andel and Wehner, 2004;Knaden and Wehner, 2005). It is neither switched off nor reset whenever the ant is foraging.…”
Section: Discussionmentioning
confidence: 99%
“…It is this feat of navigation that made C. fortis, a prime example of a solitary central place forager, a model organism for navigation (for a review, see Wehner, 2008). The key to the ants' navigational success is path integration (Müller and Wehner, 1988;Wehner, 1982; for a review, see Collett and Collett, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Even though they are confronted with only a few obvious visual landmarks in their natural environment, and therefore rely predominantly on vector navigation (for a review, see Cheng et al, 2014), many studies have shown their ability to learn and use artificial landmarks successfully (for a review, see Wehner, 2008). It is important to note that landmarks may serve different navigational purposes.…”
Section: Introductionmentioning
confidence: 99%